Gasdermin E Deletion Attenuates Ureteral Obstruction- and 5/6 Nephrectomy-Induced Renal Fibrosis and Kidney Dysfunction - Wu, Mengying; Xia, Weiwei; Jin, Qianqian; Zhou, Anning; Wang, Qian; Li, Shuzhen; Huang, Songming; Zhang, Aihua; Zhang, Yue; Li, Yuanyuan; Jia, Zhanjun (Frontiers in Cell and Developmental Biology, 2021)
Renal fibrosis contributes to kidney dysfunction in various chronic kidney diseases (CKDs). Renal fibrosis can be driven by renal tubular cell death and inflammation. Deletion of gasdermin E (GSDME), an executor of pyroptosis, has been reported to suppress renal tubular cell pyroptosis in several models of kidney injury. However, additional evidence confirming the role of GSDME in regulating renal fibrosis and kidney function in different CKDs is required. In our study, N-GSDME expression was significantly elevated in CKD models in vivo and in vitro. GSDME deletion alleviated renal fibrosis and inflammation in both UUO and 5/6 nephrectomy (5/6Nx) models along with the attenuation of renal dysfunction. N-GSDME overexpression had a detrimental effect on fibrotic responses in UUO kidneys and TGF-β1-treated renal tubular epithelial cells. In addition, administration of caspase-3 inhibitor Z-DEVD-FMK, which inhibits caspase-3-mediated GSDME cleavage, protected against renal fibrosis both in vivo and in vitro. Collectively, these results provide evidence that the activation of GSDME is critical in regulating both renal fibrosis and kidney dysfunction possibly via promoting inflammatory responses in CKD. These findings may offer new insights into the identification of new therapeutic targets for protecting against CKDs.